Senegal : Report on the Observance of Standards and Codes (ROSC) : Corporate Governance Country Assessment - World Bank (Washington, DC, 2012)
This report provides an assessment of Senegal's corporate governance policy framework, enforcement, and compliance practices. It highlights recent improvements in corporate governance regulation, makes policy recommendations, and provides investors with a benchmark against which to measure corporate governance in Senegal. The report identifies several key next steps that can be carried out in Senegal and that focus on implementation, including: (i) developing program to build awareness of the importance of corporate governance and to train directors in modern corporate governance principles; (ii) drafting a code of corporate governance; (iii) addressing governance weaknesses in the state-owned enterprises. A separate report reviews the special issues for the corporate governance of state-owned enterprises in Senegal; and (iv) revising the Organization for the Harmonization of Business Law in Africa (OHADA) uniform act for commercial companies (over the long term) to incorporate modern corporate governance principles.